Comparison of Reproductive Outcomes in ICSI Cycles Using Sperm Chip Technique and Density Gradient Technique in Men with Normal Semen Analysis - Selin Ozaltin; Hale Goksever Celik; Yucel Kocyigit; Emre Kar; Mete Gungor; John Yeh; Ercan Bastu (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: Microfluidic sperm sorting procedure or sperm chip technique is a chemical-free method of selecting sperm using a disposable chip. It is a new gentle alternative for sperm processing which has been produced to obtain sperm with higher rates of motility and better morphology, as well as to reduce DNA fragmentation in sperm with high DNA fragmentation to nearly undetectable levels. We aimed to evaluate sperm chip techniques on clinical pregnancy rates in patients who underwent intracytoplasmic sperm injection (ICSI). Methods: The patients in whom fresh embryo transfer (ET) on Day-3 or 5 after ICSI had been performed were analyzed in this prospective randomized cohort study. Results: Of those, 102 patients underwent ICSI with sperm isolated using sperm chip technique (study group) while 111 patients underwent ICSI with sperm isolated using swim-up technique (control group). No significant difference was observed between the groups in terms of fertilization rate in patients who underwent ET on the 3rd or 5th day. In the patients having ET on Day-3, Grade 1 embryos were obtained similarly between the sperm chip group and the control group. Grade 1 embryos transferred on Day-5 were observed significantly more frequently in the study group (p = 0.050). However, clinical pregnancy rates did not show significant differences between the groups in patients who were transferred on both the 3rd and 5th days. Conclusions: Although sperm selection using by sperm chip technique provides advantage in terms of blastocyst quality, use of this technique does not enhance success in terms of clinical pregnancy. Clinical Trial Registration: Approval was obtained from ClinicalTrials.gov with NCT03355937 approval number.